ANALYSIS OF THE CAUSES OF INDISCIPLINED NARCOTICS INMATES IN CLASS IIB BLITAR CORRECTIONAL INSTITUTION - Sisfani, Dila; Anwar, Umar (Universitas Nusa Cendana, 2025)
This research aims to analyze the causes of indiscipline behavior among narcotics prisoners at Class IIB Blitar Penitentiary and propose solutions to reduce the incidence of such behavior. Narcotics crimes are categorized as extraordinary crimes that significantly impact the stability within penitentiaries. Data shows that the majority of inmates in Blitar Penitentiary are narcotics offenders, who often engage in various forms of disciplinary violations such as smuggling contraband. The causes of indiscipline behavior are influenced by internal factors, such as psychological stress due to the deprivation of freedom, and external factors, such as overcrowding and a lack of social control from both families and the prison environment.The research employed a qualitative approach using a case study method. Data was collected through interviews with prisoners, prison officers, and correctional counselors, as well as direct observations in the field. The findings indicate that indiscipline violations are driven by weak social bonds between prisoners and their families or society, as well as a lack of inmate participation in constructive rehabilitation programs. The study recommends more intensive social rehabilitation programs, enhanced supervision, and inmate empowerment initiatives to reduce the risk of disciplinary violations. Consequently, narcotics prisoner rehabilitation is expected to be more effective, minimizing the rate of infractions within the penitentiary. Keywords: Narcotics Prisoners; Indiscipline Behavior; Social Control